RP-HPLC Method Validation for Purity Assay of α-Mangostin Isolate - Ratih, Ratih; Budipramana, Krisyanti; Firmansyah, Adang (Fakultas Farmasi, Universitas Surabaya, 2023)
The quality of natural products regarding the purity of their active compounds, such as α-mangostin isolate from mangosteen pericarp, may vary depending on cultivation, harvest season, and isolation process. Thus, extensive isolation procedures are involved in obtaining a certain level of purity of the active compounds. Studies on the yield of α-mangostin isolate and its effectiveness as an active compound in health care have been reported. The quality parameter of the isolate as the intended active compound can be indicated by its purity level. Measuring the purity of the active compound is proposed to define the grade α-mangostin isolate as a starting material or even reference standard. The higher the purity level of α-mangostin isolate, the greater its potential as a reference standard candidate. Therefore, a selective analytical method is required to measure the purity level accurately. For this reason, a rapid analytical method to ensure α-mangostin isolate was developed and validated to confirm its purity. Separation condition semployed an X-Terra® C18 column 5 μm, 4.6 x 150 mm under an isocratic system with a mobile phase composition of MeCN:water (85:15) at a flowrate of 0.5 mL/ min and a detector wavelength of 243 nm were selected. Acceptable validation parameters of linearity in the range of 2.6 –52 μg/mL with r2 = 0,9994, Vx0 = 2.64%; accuracy 96.38 – 100.99%; precision 1.36%; and LOD/LOQ = 4.6 μg/mL/ 13.7μg/mL were achieved. The validated method was successfully applied to the purity assay α-mangostinisolate with a run time of less than 9 minutes.